Penerapan Sistem Pneumatik Pada Alat Cetak Briket Serbuk Arang Tempurung Kelapa Sebagai Bahan Bakar Alternatif - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Abdul Syukur Alfauzi (Teknis, 2015)
Coconut shell charcoal is one of the alternative materials environmentally friendly energy. The process of making briquettes made several stages, namely, coconut shell charcoal is made by way ofÂ oven manually through later in the drum and closed until there is little ventilation in the charcoal drum. The next process of charcoal produced using diskmil and further make powderÂ coconut shell flour that has been filtered then mixed with 2.5% starch glue from coconut shell flour. After the ingredients are mixed evenly, then put into molds briquettes and then performed and the drying oven. This research aims to design and print tool making coconut shell charcoal briquettes with an automated system with pneumatic drive to improve the productivity of industrial briquettes. Display devices are planned and made briquettes have a production capacity of 36 briquettes / min size briquette diameter 30 mm, height 14 mm. Briquettes press tool has dimensions of 400 mm long, 300 mm wide, 650 mm high and 30 mm diameter, height (11-14) mm, capable of withstanding a load of 933.3 N at a temperature of 200oC for 22 minutes.Keywords: coconut shell charcoal briquets, Pneumatic